Trend analysis of rainfall and frequency of rainy days over Coimbatore (MAUSAM, 2014)
Rainfall is very crucial for the economic development, disaster management, hydrological planning for the country. In the context of climate change, it is pertinent to ascertain whether the characteristic of Indian rainfall is also changing. Using daily rainfall data for the period of 1907-2012 analysis were carried out, to find out the change in rainfall and frequency of rainfall intensity. Results indicated that the annual rainfall is not dependable. Contribution of NEM to the total rainfall is 50.3 percent which was followed by SWM (26.3%). Contribution of NEM during every 30 years of periods was constantly increasing and the increasing trend was statistically significant at 95% confidence level. Total number of rainy days (very light, light, moderate, rather heavy, heavy, very heavy rainy days) during the study period was 80.2 days, in which the frequency of very light rainy days (35.0 days) was highest followed by light (20.7 days) and moderate rainy days (20.8 days). Trend analysis was done for all categories of rainfall to find out the presence of increasing or decreasing trend. Total number of rainy days slightly gets decreasing in all the seasons except NEM where the rainy days are increasing but the changes were not statistically significant. The results showed that there is no change in long term of monthly, seasonal, annual rainfall and frequency of rainy days. Hence, it can be concluded that there is no climate change observed over Coimbatore.